2012
DOI: 10.4103/0974-777x.93762
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of an outbreak of viral hepatitis B in Modasa town, Gujarat, India

Abstract: Background:Most outbreaks of viral hepatitis in India are caused by hepatitis E. Recently in the year 2009, Modasa town of Sabarkantha district in Gujarat witnessed the outbreak of hepatitis B.Purpose:An attempt was made to study the outbreak clinically and serologically, to estimate the seropositivity of hepatitis B Virus among the cases and their contacts and to know the seroprevalence of hepatitis B envelope antigen (HBeAg) and IgM antibody against hepatitis B core antigen (IgM HBcAb) out of all the Hepatit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 14 publications
(14 reference statements)
2
26
0
1
Order By: Relevance
“…This correlates well with the observations of other researchers who investigated blood-borne viral hepatitis outbreaks (Patel et al, 2012;Verma et al, 2014). From this, we conclude that this age group, being the most productive, seeks injections more often than others for any illness, based on the belief that injections are a more effective treatment than oral medications and will achieve a faster cure and hence decrease morbidity and disability days.…”
Section: Discussionsupporting
confidence: 90%
“…This correlates well with the observations of other researchers who investigated blood-borne viral hepatitis outbreaks (Patel et al, 2012;Verma et al, 2014). From this, we conclude that this age group, being the most productive, seeks injections more often than others for any illness, based on the belief that injections are a more effective treatment than oral medications and will achieve a faster cure and hence decrease morbidity and disability days.…”
Section: Discussionsupporting
confidence: 90%
“…There was an unusually high mortality in the present outbreak. [9] Initially, co-infection with other hepatotropic viruses was considered, but, as seen in our study, co-infection with other viruses was not found to be a co-factor. Four patients with co-infection with HAV and HEV seen in our study did not show any clinical severity of the disease.…”
Section: Discussionmentioning
confidence: 68%
“…Government authorities confirmed that the mode of transmission was from continuous use of contaminated needles and syringes as well as multiple use of single-use needle and syringes by private doctors in the Modasa town and adjoining areas by interviewing the patients, their family members and their doctors. [9] Unsafe injection practices are rampant, and investigations into this outbreak may be just an indicator of a major catastrophe waiting to occur. Reuse of single-use syringes and needles by the medical practioner also brought to light an illegal network for recycling medical waste existing in the region.…”
Section: Discussionmentioning
confidence: 99%
“…397 Inadequately sterilised needles and syringes are an important cause of transmission of blood-borne hepatitis in India. 398 A large proportion of health-care workers in India are unvaccinated, many are unaware of their vaccination status, and are thus vulnerable to bloodborne infections. 399 The implementation of safe injection practices in the Indian health-care system is urgently needed.…”
Section: The Lancet Gastroenterology and Hepatology Commissionmentioning
confidence: 99%